2008
DOI: 10.1016/j.pce.2008.06.045
|View full text |Cite
|
Sign up to set email alerts
|

The river basin game as a tool for collective water management at community level in South Africa

Abstract: In the Olifants river basin about 60% of water resource is used in agriculture (DWAF, 2004). Agriculture faces increasing competition from other water users, constraining its contribution to economic growth. Spatial and temporal water shortage for irrigation affects small scale farmers resulting in conflicts on sharing the little available water. This paper presents the River Basin Game (RBG) as a tool for equitable and sustainable water resource use in the Sofaya irrigation scheme in Sekororo, Olifants in Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…A recent study of small-scale water users in the Olifants River basin in South Africa by Magombeyi, Rollin, and Lankford (2008), for instance, found that education programmes which trained farmers to become more active stakeholders in communal water-access decision making produced improved outcomes for water management and conservation (Magombeyi et al, 2008). The study indicated the particular importance of dynamic interaction amongst different stakeholders in negotiations for limited water allocation, particularly the lowest local water management institutions, such as irrigation committees comprising smallholder farmers.…”
Section: Improving Water Management Practices: Current Trends and Issuesmentioning
confidence: 99%
“…A recent study of small-scale water users in the Olifants River basin in South Africa by Magombeyi, Rollin, and Lankford (2008), for instance, found that education programmes which trained farmers to become more active stakeholders in communal water-access decision making produced improved outcomes for water management and conservation (Magombeyi et al, 2008). The study indicated the particular importance of dynamic interaction amongst different stakeholders in negotiations for limited water allocation, particularly the lowest local water management institutions, such as irrigation committees comprising smallholder farmers.…”
Section: Improving Water Management Practices: Current Trends and Issuesmentioning
confidence: 99%
“…The game serves as a simplified metaphor for the Jordan River Basin and a methodological tool to observe human behaviour in decisionmaking processes of water cooperation. River basin boardgames distil the main dimensions of ecological and human processes in a conceptual hydrological model (Lankford 2007, Magombeyi 2008. Bruce Lankford (2007) has contributed greatly to natural resource gaming with his River Basin Game as a dialogue tool for decision makers and water users of surface water resources.…”
Section: The Jordan River Boardgame Exercise (Jrbbe)mentioning
confidence: 99%
“…Some MSG have been used effectively however as intervention method with local stakeholders at a community level, for instance with local farmers or fishermen in rural areas of developing countries. See for a few examples: [33,36,40,41].…”
Section: Introductionmentioning
confidence: 99%